2000
DOI: 10.2460/ajvr.2000.61.1214
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray absorptiometry measurement of bone-mineral density in the distal aspect of the limbs in racing Greyhounds

Abstract: Asymmetric adaptive remodeling of metacarpal 5 can be detected by DXA. The potentially confounding effects of CTB fracture and unknown racing history made it difficult to interpret BMD changes in the CTB of these specimens. Densitometry could be developed as an in vivo assessment for risk of fractures in racing Greyhounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…DXA technology is a combination of a pencil-beam X-ray absorptiometry and a sophisticated analytic computer software. Many studies (Markel et al, 1994;Emmerson et al, 2000;Lauten et al, 2001) proved that software designed for humans could be used successfully in larger-sized animals like dogs, sheep and pigs. However, since our animals were puppies weighing less than 10 kg, we applied the Low Density Programme that is used in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DXA technology is a combination of a pencil-beam X-ray absorptiometry and a sophisticated analytic computer software. Many studies (Markel et al, 1994;Emmerson et al, 2000;Lauten et al, 2001) proved that software designed for humans could be used successfully in larger-sized animals like dogs, sheep and pigs. However, since our animals were puppies weighing less than 10 kg, we applied the Low Density Programme that is used in children.…”
Section: Discussionmentioning
confidence: 99%
“…One of these techniques is dual energy X-ray absorptiometry (DXA), which has become a standard procedure for noninvasive evaluation of body composition in research and clinical medicine in humans. Few publications (Emmerson et al, 2000;Lauten et al, 2001) have directly addressed its use for clinical research in dogs and other companion or farm animals. In dogs, DXA has been used for research into fracture healing, bone strength, and other physical properties of bone (Lauten et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier observations (Emmerson andothers 2000, Johnson andothers 2001) suggested that the fifth metacarpal bone undergoes microstructural and densitometric adaptation. In this study, the mechanical and densitometric responses of the fifth metacarpal bone to asym-metric cyclic loading have been investigated in greyhounds with and without a fracture of the right central tarsal bone.…”
mentioning
confidence: 91%
“…This leads to site‐specific soft tissue and bone remodelling (Emmerson et al . , Johnson et al . , Lipscombe et al .…”
Section: Introductionmentioning
confidence: 99%